1995
DOI: 10.1227/00006123-199502000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Meningiomas in the 9th Decade of Life

Abstract: The general availability of cerebral computed tomographic and magnetic resonance imaging scans makes the observation of symptomatic intracranial meningiomas in very elderly patients (aged 80 yr or more) relatively frequent. A few authors have reported on patients who have undergone surgery for intracranial meningiomas in their 9th decade of life, without providing indications regarding the surgical criteria and the prognostic factors. We report on a series of 17 patients who have received surgery for intracran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(21 citation statements)
references
References 12 publications
2
19
0
Order By: Relevance
“…Several recent large studies have suggested increasing age as a prognostic risk factor in patients indicated for intracranial meningioma surgery, 13,14,16,32,52) but clinical and functional status 1316,18,32,34,5355) and radiological features 13,17,25,32,53,54,56,57) are still more frequently recognized as risk factors. Moreover, female sex has been associated with better prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent large studies have suggested increasing age as a prognostic risk factor in patients indicated for intracranial meningioma surgery, 13,14,16,32,52) but clinical and functional status 1316,18,32,34,5355) and radiological features 13,17,25,32,53,54,56,57) are still more frequently recognized as risk factors. Moreover, female sex has been associated with better prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…1. From a total of 1039 articles, seven fulfilled the inclusion criteria [5,6,14,15,19,20,23]. All seven studies were retrospective, conducted between 1995 and 2018.…”
Section: Resultsmentioning
confidence: 99%
“…All seven studies were retrospective, conducted between 1995 and 2018. Three of the studies were performed in Italy [5,6,15], two in France [19,20], one in Norway [14], and one in the USA [23]. The latter [23] was based on a large national register (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations